IMPLEMENTASI BUILDING INFORMATION MODELING (BIM) DALAM PERENCANAAN DIMENSI SALURAN DRAINASE DI UB FOREST SUMBERSARI - Listyana, Kurnia Ulfi; Dermawan, Very; Cahya, Evi Nur (JURNAL SUMBER DAYA AIR, 2024)
UB Forest Sumbersari is a forest for multidisciplinary research and development in Brawijaya University. In order to improve and reducing the environmental damage around the road due to water flow, the planned drainage system by implementing BIM. BIM has a major role in coordinating and integrating information exchange and knowledge between various disciplines and phases in the project implementation. In this study, the Autodesk Civil 3D and Autodesk Storm and Sanitary Analysis (SSA) are employed as a BIM platform. Autodesk Civil 3D is the latest version of AutoCAD Land Desktop development that has used the dynamic modeling concept. Autodesk Civil 3D helps facilitate in case of design changes as well as in the calculating of job volume such as the volume of cut and fill of the soil and volume of required materials in drainage channel planning. While SSA facilities plan on hydraulics such as flow depth, maximum velocity, channel slope, and channel dimensions. Based on the result of the SSA analysis, the dimensions of drainage channel are 30 cm x 30 cm, 50 cm x 50 xm, 65 cm x 65 cm, and 80 cm x 80 cm. And generated volume of cut equals to 3148,02 m3, while the volume of fill equals to  296,93 m3, with total required volume of gravel reaches 444,8 m3. Keywords:   drainage, Building Information Modeling, Autodesk Civil 3D, Storm and Sanitary Analysis,  UB Forest Sumbersari